2015
DOI: 10.1007/s13679-015-0168-5
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Relationship Between Socioeconomic Position and the Early-Life Predictors of Obesity

Abstract: A range of important early-life predictors of later obesity have been identified. Children of lower socioeconomic position (SEP) have a steeper weight gain trajectory from birth with a strong socioeconomic gradient in child and adult obesity prevalence. An assessment of the association between SEP and the early-life predictors of obesity has been lacking. The review involved a two-stage process: Part 1, using previously published systematic reviews, we developed a list of the potentially modifiable determinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 133 publications
(148 reference statements)
6
82
0
1
Order By: Relevance
“…The association between parental SES and CP may operate through mediating lifestyle factors, such as poor diet, obesity, type 2 diabetes, cigarette smoking and psychosocial factors. All of these have been associated with SES, 19 , 27 and obesity and smoking increased the risk of CP in large prospective studies conducted in Denmark, Norway and Sweden, 28–31 whereas the role of dietary factors, type-2 diabetes and psychosocial factors in CP have been less explored. Other potential mediating factors include genitourinary infections and use of paracetamol during pregnancy; both differed by socioeconomic status and were associated with risk of CP in three large prospective Danish studies 28 , 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The association between parental SES and CP may operate through mediating lifestyle factors, such as poor diet, obesity, type 2 diabetes, cigarette smoking and psychosocial factors. All of these have been associated with SES, 19 , 27 and obesity and smoking increased the risk of CP in large prospective studies conducted in Denmark, Norway and Sweden, 28–31 whereas the role of dietary factors, type-2 diabetes and psychosocial factors in CP have been less explored. Other potential mediating factors include genitourinary infections and use of paracetamol during pregnancy; both differed by socioeconomic status and were associated with risk of CP in three large prospective Danish studies 28 , 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in children also showed that, in developed countries, obesity was more prevalent in lower-income people, but in developing countries it was more common in higher-income people [22]. On the other hand, as SES changes during life, risk of obesity changes accordingly [23].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we do not have information about maternal BMI in order to explore its impact on offspring BMI and WC. Moreover, there are many environmental determinants and psychological factors involved to the predictors of obesity which mediate the association with LBW, such as maternal cigarette smoking, maternal education and inadequate maternal nutrition [46]. Regarding gender differences in social patterning, social childhood exposure seems to influence later life outcomes, including biological programming during critical periods of growth and the early acquisition an unhealthy lifestyle [47].…”
Section: Discussionmentioning
confidence: 99%